2012
DOI: 10.1109/tit.2012.2191388
|View full text |Cite
|
Sign up to set email alerts
|

Aligned Interference Neutralization and the Degrees of Freedom of the 2$\,\times \,$2$\,\times \,$2 Interference Channel

Abstract: We show that the 2 × 2 × 2 interference network, i.e., the multihop interference network formed by concatenation of two 2-user interference channels achieves the min-cut outer bound value of 2 DoF, for almost all values of channel coefficients, for both time-varying or fixed channel coefficients. The key to this result is a new idea, called aligned interference neutralization, that provides a way to align interference terms over each hop in a manner that allows them to be cancelled over the air at the last hop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
316
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 185 publications
(318 citation statements)
references
References 58 publications
2
316
0
Order By: Relevance
“…Since the min-cut DoF outer bound is 2, we only need to provide an achievable scheme to achieve 2 DoF for this channel. Recall that for the 2 × 2 × 2 IC where two relays do not interfere with each other, 2 DoF can be achieved using aligned interference neutralization [7]. As we can see, the only difference between the 2 × 2 × 2 IC studied in [7] and the channel studied in this paper is the additional assumption that two relays are interfering with each other.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Since the min-cut DoF outer bound is 2, we only need to provide an achievable scheme to achieve 2 DoF for this channel. Recall that for the 2 × 2 × 2 IC where two relays do not interfere with each other, 2 DoF can be achieved using aligned interference neutralization [7]. As we can see, the only difference between the 2 × 2 × 2 IC studied in [7] and the channel studied in this paper is the additional assumption that two relays are interfering with each other.…”
Section: Resultsmentioning
confidence: 82%
“…While the DoF for the general cases are not known, some progress has been made for some special cases. In [7], it is shown that the 2×2×2 interference network, i.e., the 2-hop interference network formed by concatenation of two 2-user interference channels, achieves the cut-set outer bound value of 2 DoF for almost all channel coefficients. Although the 2 × 2 × 2 setting seems special, the new idea of aligned interference neutralization that emerged out of the study of this channel turns out to be important to achieve the optimal DoF of a variety of multihop multiple unicast networks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relay and interference alignment algorithm, can greatly improve the system capacity. Interference alignment algorithm for 2L + 1X relay network [46] proposed an alignment of interference and mechanisms. The basic idea is aligned each hop in the network interference, and interference cancellation at the last hop.…”
Section: Relay Technologymentioning
confidence: 99%